A sustainable food hub to enhance community nutrition through urban crop production in Las Piñas - Sanchez, Andrea Cecilia R. (College of Architecture, University of the Philippines Diliman, 2022)
Urban food systems continue to face challenges along with urbanization. With this, the negative climate change effects have compounded and exacerbated the issues faced by urban communities. In the context of Metro Manila, rapid urbanization and the current state of the food supply chain have been identified as causes of fragility in urban food systems. Rapid urbanization results in a dietary shift to nutrient-poor foods as it becomes more convenient and accessible. In turn, negative health effects due to undernutrition are becoming more prominent in urban dwellers. As for the food supply chain, its current state is characterized by: food production sourced in rural areas which are vulnerable to natural disasters; traditional food production that has significant negative environmental impacts; inefficient farm-to-market roads; and inaccessible food products due to high price points. Furthermore, the perceived issues in the urban food system are narrowed down to three major problems: malnutrition, unstable food supply, and negative environmental impacts of the existing urban food system.The aforementioned issues are then contrasted against the Sustainable Food System (FAO ,2014) with a focus on parameters of the Resilient Food System (FAO ,2020). This thesis will conduct contextual study of the site located at the district 1 of Las Piñas as it is deemed to be the location of the first translation of the research and integrate concepts from the food systems frameworks. Furthermore, the goal of this study is to provide urban communities with access and stable supply of vegetable crops which is a component of an individual’s dietary needs through an in-city food production. This can be done through controlled-environment agriculture. In addition, the study has a goal to reduce negative environmental impacts caused by the existing urban food system along with a food system resilience feature. With these goals, the research ultimately proposes a sustainable food hub that enhances community nutrition.